Using cluster of differentiation CD 38, CD 45 and CD 95 as a method of primary diagnosis of uterine fibroids - Savytskyi, I. V.; Magdenko, G. K.; Miastkívska, I. V.; Orel, K. S.; Grigoriev, P. E.; Chernysh, L. N. (Journal of Education, Health and Sport, 2017)
Uterine myoma is one of the first places among gynecological diseases. There is a rise of the number of pathology diagnoses among young women. Currently inUkrainethere is no single approved laboratory method for screening of uterine myomas. The aim of our work is the studying of the efficiency of CD38, CD45, and CD95 leukocyte differentiation clusters for early detection of uterine myomas. Determination of a subpopulation of lymphocytes in urine with immune complex of peroxidase-antiperoxidase. The features of the number of leukocytes with CD 38, CD 45, CD 95 antigens were analyzed among women with uterine myoma compared with women who did not have gynecological diseases and underwent an appropriate research. Each sample consisted of 50 women aged 30 to 65 years (average age in both samples was 45 years). The Student's test for independent samples was used for statistical methods of comparison. The results we’ve got indicate that the most statistically significant differences were established by SD 95, so it can be assumed that it is the one that is the most informative as a possible marker for the presence of uterine fibroids. At the same time, during the analyzingof the clusters of CD38 and CD45 differentiation, there were also found highly significant differences between the group of patients with uterine myoma and healthy women.